Dairy product consumption and type 2 diabetes in an Argentinian population: Is there an association? - Baraquet, María Lucía (2023)
Introduction: dairy products have long been recommended as part of a healthy eating plan, but there is a controversial opinion about whether or not they should be included in the diet of people with type 2 diabetes (T2D). Objective: the aim of this study was to know if there is an association between the intake of total dairy and dairy subgroups and the chance of having T2D, and the status of markers of glucose metabolism. Methods: three hundred and forty-two adult subjects participated in the study. A validated food-frequency questionnaire was applied to establish the dairy intake. Clinical-pathological and anthropometric variables (height, weight, waist circumference and serum concentrations of blood glucose, glycated hemoglobin [HbA1c], high sensitive C-reactive protein [hs-CRP], tumor necrosis factor alpha [TNFα], interleukin [IL] 6 and IL-10) were measured. Consumption tertiles were calculated for each dairy subgroup. Correlation coefficients, multiple linear regression models and logistic regression models were used to assess the relation between dairy product consumption and markers of glucose metabolism. Results: a negative correlation was observed between the consumption of fermented dairy products and IL-10 (r = -0.27, p = 0.0206). Fermented dairy products were inversely associated with blood glucose, and HbA1c. Total dairy intake was positively associated with a lower chance of having diabetes in tertiles 2 and 3 of consumption, in relation to the reference tertile, adjusted for age, smoking habit, and alcohol intake, body mass index (BMI) and dietary variables. Conclusions: with this study, we broaden our understanding of the role of dairy intake in diabetes risk. However, more long-term studies are needed to confirm the associations and explore different confounding factors.